2017
DOI: 10.1111/1468-5973.12186
|View full text |Cite
|
Sign up to set email alerts
|

The complexities of place in crisis renewal discourse: A case study of the Sandy Hook Elementary School shooting

Abstract: The discourse of renewal is an established strategy for crisis recovery. The current analysis examines the role that place plays in postcrisis communication, in general, and the discourse of renewal, specifically. We describe the extent to which place‐bound crises affect the ability of an organization to enact a discourse of renewal. We propose a modification of renewal discourse to include place as a condition that may make the successful enactment of renewal rhetoric more likely. Specifically, we argue that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Furthermore, in this study, we showed how the renewal narrative can facilitate positive coping responses during crises; past research has emphasized the role of the discourse of renewal in recovery crisis communication (e.g. Manzie, 2018;Ulmer et al, 2007;Wombacher et al, 2018).…”
Section: Perceived Information Credibility and Narrativesmentioning
confidence: 51%
See 1 more Smart Citation
“…Furthermore, in this study, we showed how the renewal narrative can facilitate positive coping responses during crises; past research has emphasized the role of the discourse of renewal in recovery crisis communication (e.g. Manzie, 2018;Ulmer et al, 2007;Wombacher et al, 2018).…”
Section: Perceived Information Credibility and Narrativesmentioning
confidence: 51%
“…Through renewal discourse, organizational leaders can build strong relationships with their communities (Xu, 2018). Additionally, renewal discourse offers a fresh start for an organization, community, or other group after a crisis occurs (Manzie, 2018;Wombacher et al, 2018).…”
Section: Renewal Narrativesmentioning
confidence: 99%
“…Prior research indicates that renewal has four important elements: organizational learning, prospective vision, ethical communication, and effective organizational rhetoric. Both qualitative (Sellnow et al, 2017; Wombacher et al, 2018) and quantitative research approaches (Xu, 2018) support four dimensions of postcrisis renewal. According to our research, in the precrisis stage, the most significant factors that contribute to organizational readiness for renewal are communicating ethically and effectively.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 20 years, Discourse of Renewal studies have examined cases of organizational and community responses after crises, including earthquakes (Sellnow et al, 2017), oil spills (Nelson & Reierson, 2012-2013), mass shootings (Wombacher, Herovic, Sellnow, & Seeger, 2018), and terrorist attacks (Veil, Sellnow, & Heald, 2011). There has also been some initial scale development in this research area.…”
Section: Measurement Of Readiness For Renewal In the Precrisis Stagementioning
confidence: 99%
“…The concept of "hope" fits within the recent discourse of renewal research. This theory states that circumstances can ask for a prospective outlook that emphasizes positive change during the post-crisis period (Wombacher et al, 2018). The post-crisis discourse of renewal is characterized by four dominant features: prospective focus, the opportunities inherent in the crisis, provisional rather than strategic responses, and ethical communication grounded in core values (Seeger & Ulmer, 2002;Seeger et al, 2005;Ulmer & Sellnow, 2002).…”
Section: Promote Hopementioning
confidence: 99%